FULFILLING CONSUMER RIGHTS FOR MSMES IN CIBOGO VILLAGE AS AN EFFORT TO INCREASE TOURIST ATTRACTION - Rafan Darodjat; Deviana Yuanitasari; Helza Novianty (Ikatan Dosen Menulis, 2024)
Cibogo Village has great tourism potential due to its location in North Bandung, at the foot of Mount Tangkuban Perahu. Service activities aim to inspire MSMEs, communities, and village officials to enhance tourism potential by considering tourists as consumers whose rights need to be fulfilled. Hospitality, quality products, and a harmonious community environment will attract tourists. This collective effort by the entire community is necessary to create a unique attraction. The service activities are implemented through counseling and mentoring by the PPM Team, integrated with Unpad Student KKN activities. The team intensively assists 15 MSMEs in Cibogo Village. The research results indicate an increase in tourist attraction in Cibogo Village following the promotion of consumer rights. The study demonstrates that promoting consumer rights can enhance tourist attraction by increasing MSMEs' knowledge and understanding of these rights and building consumer trust in the products and services offered by MSMEs in Cibogo Village.